Effect of angiotensin‐converting enzyme inhibition on cardiovascular adaptation to exercise training. Issue 13 (13th July 2022) - Sjúrðarson, Tórur; Bejder, Jacob; Breenfeldt Andersen, Andreas; Bonne, Thomas; Kyhl, Kasper; Róin, Tóra; Patursson, Poula; Oddmarsdóttir Gregersen, Noomi; Skoradal, May‐Britt; Schliemann, Michael; Lindegaard, Malte; Weihe, Pál; et al.
Abstract: Angiotensin‐converting enzyme (ACE) activity may be one determinant of adaptability to exercise training, but well‐controlled studies in humans without confounding conditions are lacking. Thus, the purpose of the present study was to investigate whether ACE inhibition affects cardiovascular adaptations to exercise training in healthy humans. Healthy participants of both genders (40 ± 7 years) completed a randomized, double‐blind, placebo‐controlled trial. Eight weeks of exercise training combined with placebo (PLA, n = 25) or ACE inhibitor (ACEi, n = 23) treatment was carried out. Before and after the intervention, cardiovascular characteristics were investigated. Mean arterial blood pressure was reduced ( p < 0.001) by −5.5 [−8.4; −2.6] mmHg in ACEi, whereas the 0.7 [−2.0; 3.5] mmHg fluctuation in PLA was non‐significant. Maximal oxygen uptake increased ( p < 0.001) irrespective of ACE inhibitor treatment by 13 [8; 17] % in ACEi and 13 [9; 17] % in PLA. In addition, skeletal muscle endurance increased ( p < 0.001) to a similar extent in both groups, with magnitudes of 82 [55; 113] % in ACEi and 74 [48; 105] % in PLA. In contrast, left atrial volume decreased ( p < 0.05) by −9 [−16; −2] % in ACEi, but increased ( p < 0.01) by 14 [5; 23] % in PLA. Total hemoglobin mass was reduced ( p < 0.01) by −3 [−6; −1] % in ACEi, while a non‐significant numeric increase of 2 [−0.4; 4] % existed in PLA. The lean mass remained constant in ACEi but increased ( p < 0.001) by 3 [2; 4] % in PLA. In healthy middle‐aged adults, 8 weeks of high‐intensity exercise training increases maximal oxygen uptake and skeletal muscle endurance irrespective of ACE inhibitor treatment. However, ACE inhibitor treatment counteracts exercise training‐induced increases in lean mass and left atrial volume. ACE inhibitor treatment compromises total hemoglobin mass. Abstract : A high‐intensity endurance exercise training program improves maximal oxygen uptake, whole‐body work capacity, and muscle endurance, with no effect of ACE inhibitor treatment, in normotensive adults. However, ACE inhibitor treatment impairs the exercise‐induced increase in lean mass and left atrial volume and compromises total hemoglobin mass. Results are presented as means with 95% confidence intervals. * p < 0.05, ** p < 0.001 for the within‐group change (∆) from baseline from a paired samples t‐test, and # p < 0.05 for the between‐group difference in change from baseline from an independent samples t‐test in participants treated with an angiotensin‐converting enzyme inhibitor (ACEi ) or placebo. CMR, cardiovascular magnetic resonance imaging.